How Does Psychological Distance Influence Public Risky Behavior During Public Health Emergencies - Gao Y; Sun Y (Dove Medical Press, 2024)
Yu Gao,1 Yuechi Sun2 1School of Psychology, Shandong Second Medical University, Weifang, Shandong, People's Republic of China; 2School of Economics and Management, China University of Geosciences (Beijing), Beijing, People's Republic of ChinaCorrespondence: Yu Gao, School of Psychology, Shandong Second Medical University, 7166 Baotong West Street, Weicheng District, Weifang, Shandong, 261053, People's Republic of China, Email gaoyucugb@163.comBackground: Public health emergencies not only threaten the physical and mental health of the public but also trigger a series of risky behaviors of the public, which in turn lead to the emergence or intensification of risk events, disrupting existing economic and social order.Purpose: Based on construal level theory, cognitive appraisal theory of emotions and mood maintenance hypothesis, the study aims to investigate the collectively effect of risk perception and psychological insecurity in the connection between psychological distance and public risky behavior.Participants and Methods: Cross-sectional data was derived from 257 China urban residents. All participants finished the psychological distance scale, risk perception scale, psychological insecurity scale, and risky behavior scale. The research hypothesis was tested using the PROCESS macro.Results: The direct impact of psychological distance on risky behavior was not significant (β=− 0.018, p> 0.05). The indirect impact of psychological distance on risky behavior was significant. In other words, the impact of psychological distance on risky behavior was serially mediated via risk perception and psychological insecurity (β=0.011, 95% CI= [0.0013, 0.025]).Conclusion: Risk perception and psychological insecurity play serial mediating roles in the relationship between psychological distance and public risky behavior. We conclude that during public health emergencies, public health managers should pay extra attention to the risk perception and psychological insecurity level of the public with closer psychological distance, take measures to reduce their risk perception, enhance their psychological security, and reduce their risky behavior, thereby ensuring the physical and mental health of the public and maintaining the stability of economic and social order.Keywords: public health emergencies, psychological distance, risk perception, psychological insecurity, risky behavior